A Facile Hydrothermal Synthesis and Electrochemical Properties of Manganese dioxide@graphitic Carbon Nitride Nanocomposite toward Highly Sensitive Detection of Nitrite. Issue 14 (16th September 2019) - Keerthi, Murugan; Manavalan, Shaktivel; Chen, Shen-Ming; Shen, Pei-Wun
Abstract : The present work describes an electrochemical detection of nitrite by using screen-printed carbon electrode (SPCE) modified manganese dioxide@graphitic carbon nitride nanocomposite (MnO2 @g-C3 N4 ). The MnO2 @g-C3 N4 nanocomposite was successfully prepared by a facile low-temperature hydrothermal process and characterized using XRD, FT-IR, N2 adsorption- desorption isotherm, XPS, FE-SEM, HR-TEM, and EIS. The nanocomposite exhibited excellent synergistic effect and enhanced electrocatalytic activity than electrodes modified with MnO2 and g-C3 N4 . In comparison to cyclic voltammetry (CV) results of bare SPCE and modified SPCEs, the large electrochemical current difference was achieved in MnO2 @g-C3 N4 nanocomposite electrode for nitrite detection. The differential pulse voltammetry was used to determine the nitrite and the voltammetric response of nitrite was linear over the 0.01–1520 μM with a low detection limit (LOD) of 1.23 nM (S/N = 3) and high sensitivity of 24.1777 μAμM −1 cm −2, which are much better than the results reported so far for electrochemical nitrite detection. The MnO2 @g-C3 N4 nanocomposite electrode also revealed high selectivity of nitrite detection in the presence of potentially interfering compounds even in high concentration. As proof of this method, the practicability of the sensors was examined in tap water, drinking water and rotten beef samples and revealed acceptable recovery for the determination of nitrite.